Dysregulated cytokine and oxidative response in hyper-glycolytic monocytes in obesity - Radushev, Veselina; Karkossa, Isabel; Berg, Janina; von Bergen, Martin; Engelmann, Beatrice; Rolle-Kampczyk, Ulrike; Blüher, Matthias; Wagner, Ulf; Schubert, Kristin; Rossol, Manuela (Frontiers in Immunology, 2024)
Obesity is associated with a plethora of health complications, including increased susceptibility to infections or decreased vaccine efficacy, partly due to dysregulated immune responses. Monocytes play a crucial role in innate immunity, yet their functional alterations in obesity remain poorly understood. Here, we employed proteomic and metabolomic analyses to investigate monocyte characteristics in individuals with overweight, obesity, impaired glucose tolerance (IGT), and type 2 diabetes (T2D), compared to lean donors. Our results revealed distinct molecular signatures in monocytes from individuals with obesity, with significant alterations in pathways related to metabolism, cellular migration, and phagocytosis. Moreover, LPSinduced activation of monocytes unveiled heightened metabolic reprogramming towards glycolysis in subjects with obesity accompanied by dysregulated cytokine responses and elevated oxidative stress. Additionally, monocytes from donors with obesity exhibited increased lipid droplet accumulation. These findings shed light on the immunometabolic dysregulation underlying obesity-associated immune dysfunction, highlighting potential targets for therapeutic intervention.